2006
DOI: 10.1111/j.1574-695x.2006.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of synthetic saccharide fragments ofVibrio choleraeO1 (Ogawa and Inaba) bound to Exotoxin A

Abstract: Recombinant exotoxin A (rEPA) from Pseudomonas aeruginosa conjugated to Vibrio cholerae O1 serotype-specific polysaccharides (mono-, di- and hexasaccharide) were immunogenic in mice. Monosaccharide conjugates boosted the humoral responses to the hexasaccharide conjugates. Prior exposure to purified Ogawa lipopolysaccharide (LPS) enabled contra-serotype hexasaccharide conjugates to boost the vibriocidal response, but Inaba LPS did not prime for an enhanced vibriocidal response by a contra-serotype conjugate. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Furthermore, they compared immunologically the P. aeruginosa rEPA conjugates of Ogawa and Inaba serotype O -antigen oligosaccharides and found that the conjugates of Ogawa oligosaccharides boosted Inaba-primed mice, whereas the conjugates of Inaba oligosaccharides could not boost Ogawa-primed mice. This result implies that Ogawa and Inaba LPSs contain different immunodominant epitopes …”
Section: Semi- and Fully Synthetic Carbohydrate-based Antibacterial C...mentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, they compared immunologically the P. aeruginosa rEPA conjugates of Ogawa and Inaba serotype O -antigen oligosaccharides and found that the conjugates of Ogawa oligosaccharides boosted Inaba-primed mice, whereas the conjugates of Inaba oligosaccharides could not boost Ogawa-primed mice. This result implies that Ogawa and Inaba LPSs contain different immunodominant epitopes …”
Section: Semi- and Fully Synthetic Carbohydrate-based Antibacterial C...mentioning
confidence: 91%
“…This result implies that Ogawa and Inaba LPSs contain different immunodominant epitopes. 214 The first emergence of a new V. cholerae serotype O139 was noticed in the southern part of India in 1992 and becomes the non-O1 V. cholerae serotype to cause epidemic cholera. 215 V. cholerae O139 possess a high molecular weight CPS, in distinctive composition from the LPS antigen.…”
Section: Acs Infectiousmentioning
confidence: 99%
“…In a subsequent study, the hexasaccharides corresponding to Ogawa and Inaba serotypes of V. cholerae O:1 were prepared by a [4 + 2] assembling strategy, converted into their squaric acid derivatives and conjugated with recombinant exotoxin A from Pseudomonas aeruginosa (rEPA) 64. The results of the immunological tests highlighted the fact that Ogawa and Inaba LPS contain different immunodominant epitopes: Ogawa neoglycoconjugates can boost Inaba‐primed mice, but Inaba neoglycoconjugates cannot boost Ogawa‐primed mice 65. More recently, an improved synthetic approach to the Ogawa terminal hexasaccharide was described by the same authors.…”
Section: Antibacterial Vaccinesmentioning
confidence: 99%
“…OSP is attached to lipid A that is part of the outer membrane of V. cholerae [9]. We have previously shown that a synthetic neoglyconjugate cholera vaccine containing a hexasaccharide of V. cholerae O1 Ogawa is protectively immunogenic in mice [10][12]. We were therefore interested in evaluating whether a cholera conjugate vaccine containing native OSP recovered from V. cholerae O1 would also be immunogenic.…”
Section: Introductionmentioning
confidence: 99%